2013
DOI: 10.1007/s11356-012-1444-5
|View full text |Cite
|
Sign up to set email alerts
|

Adverse birth outcomes in the vicinity of industrial installations in Spain 2004–2008

Abstract: Industrial activity is one of the main sources of ambient pollution in developed countries. However, research analyzing its effect on birth outcomes is inconclusive. We analyzed the association between proximity of mother's municipality of residence to industries from 24 different activity groups and risk of very (VPTB) and moderate (MPTB) preterm birth, very (VLBW) and moderate (MLBW) low birth weight, and small for gestational age (SGA) in Spain, 2004-2008. An ecological study was defined, and a "near vs. fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…In fitting the model, we took advantage of the computational efficiency of Integrated Nested Laplace Approximations (INLA, version 0.0-1420281647) estimation techniques as implemented in the well-established R-INLA package (Rue et al, 2015), which has been used in several recent studies of large dimensions (Bennett et al, 2014;Castelló et al, 2013;Lee et al, 2013;Lee and Mitchell, 2014). The INLA approach avoids the computational burden related to typical Markov Chain Monte Carlo techniques (Gilks et al, 1998) often used to fit Bayesian spatial models and allows accurate approximations to posterior marginal distributions of the model parameters (Grilli et al, 2014).…”
Section: Multilevel Spatial Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…In fitting the model, we took advantage of the computational efficiency of Integrated Nested Laplace Approximations (INLA, version 0.0-1420281647) estimation techniques as implemented in the well-established R-INLA package (Rue et al, 2015), which has been used in several recent studies of large dimensions (Bennett et al, 2014;Castelló et al, 2013;Lee et al, 2013;Lee and Mitchell, 2014). The INLA approach avoids the computational burden related to typical Markov Chain Monte Carlo techniques (Gilks et al, 1998) often used to fit Bayesian spatial models and allows accurate approximations to posterior marginal distributions of the model parameters (Grilli et al, 2014).…”
Section: Multilevel Spatial Modelingmentioning
confidence: 99%
“…Some air pollution and birth outcome studies have accounted for spatial dependency in the residuals, but still assume a global effect due to exposure (Berrocal et al, 2011;Castelló et al, 2013;Thompson et al, 2014;Williams et al, 2007). A spatial correlated autoregressive (CAR) model has been applied by (Berrocal et al, 2011) to examine the effect of CT-level PM 2.5 on continuous birth weight in North Carolina.…”
Section: Spatial Dependency Air Pollution and Birth Outcome Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been shown that local factors other than socioeconomic may be important when identifying risks factors for prematurity and low birth weight (Crosse et al 1997;Walsh et al 2010). On the other hand, some studies have suggested a possible association between residential proximity to industries and adverse birth outcomes (Morgan et al 2004;Ahern et al 2011;Castello et al 2013). In this sense, it could be useful to consider the remarkable disparity between Asturias and Murcia in terms of industrial activity to assess the significance of the differences found and potential risk factors associated.…”
Section: Resultsmentioning
confidence: 99%